The Effect of Financial Ratio on Financial Distress in Banking Companies Listed on The IDX Year 2018–2022 - Damianus Nakula Aji Irwanto; Lia Rachmawati; Mainatul Ilmi (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
The number of banks are trying to sell their assets that had deteriorated before the Covid-19 pandemic through bulksales or wholesale sales. This step is expected to immediately reduce the bank's Non-Performing Loan (NPL) ratio significantly. One of them is PT Bank Tabungan Negara Tbk (BTN). The bank is exploring the sale of NPLs in bulksales through an asset swap scheme or exchanging assets for securities. The purpose of the study was to analyze the effect of CAR, NPL, LDR, ROA, DAN BOPO partial and simultaneous events on Financial Distress in banking companies listed on the IDX in 2018 – 2022. The sample selection method uses the Purposive Sampling method so as to get 35 banking companies. The research method uses multiple linear regression analysis. The results of this study show that (1) CAR, LDR, ROA have a significant positive effect on Financial Distress (2) NPL, BOPO have no significant effect on Financial Distress (3) CAR, NPL, LDR, ROA, DAN BOPO simultaneously affect Financial Distress